Age at death and rectangularisation of the survival curve: trends in Switzerland, 1969-1994. Issue 7 (July 1998) - Paccaud, F; Sidoti Pinto, C; Marazzi, A; Mili, J
Abstract : OBJECTIVE: To check if signs of rectangularisation of the survival curve appeared during recent decades in Switzerland–that is, if life expectancy is approaching a maximum with a clustering of age at death around an average value (the so called "compression of mortality"). METHODS: Descriptive analysis of age of death and its trends over 26 years, as characterised by the modal value, median, and various percentiles beyond the median. POPULATION: All deaths occurring after the 50th birthday in Switzerland between 1969 and 1994 (n = 1, 390, 362). MAIN RESULTS: Age at death is increasing at a sustained rate at all percentiles equal or greater than 50, without any slow down in the trend during this period. The increase is more marked among women. Rates of increase are diminishing as the percentiles of age at death are higher, suggesting some clustering of deaths beyond the median value. However, the maximum age at death, if any, seems to be far from the current median values, even for women who enjoy a relatively high median age at death.